Normative beliefs about aggression: a scale validation and consideration about gender differences - Souza Filho, Marcilio Lira de; Araújo, Alessandra Gusmão Trajano de; Lima, Flávio Lúcio Almeida; Sousa, Deliane Macedo Farias de (Paidéia (Ribeirão Preto), 2005)
Normative beliefs are defined like a type of self-regulated belief of the socially appropriate behaviors. This study aimed to validate for the Brazilian context the Normative Beliefs about Aggression Scale, as well as to observe how those beliefs differs as for the gender. A sample of 201students for the 5th to 8th grade, from João Pessoa (PB), participated in this study, and their mean age was 15 years (SD = 2,0). The results indicated the measure reliability, with a multifactorial solution composed by: General approval of the Aggression, Verbal Aggression by Weak Provocation, Physical Aggression by Weak Provocation and Physical Aggression by Strong Provocation. Among these factors, the boys presented statistically higher means in the three factors. For analysis of those results it should be taken into account the type and the situation in which the conflict happens for each factor, as well as the different behavioral scripts, for male and female, assumed by the appraisers of each situation.